Pengembangan model blended learning menggunakan aplikasi Edmodo untuk mata pelajaran geografi SMA - Muhammad Alwan (Jurnal Inovasi Teknologi Pendidikan, 2017)
Tujuan penelitian ini adalah untuk menghasilkan: (1) model blended learning menggunakan Edmodo, (2) tingkat kelayakan model blended learning menggunakan Edmodo pada mata pelajaran geografi, (3) keefektifan model blended learning dengan menggunakan Edmodo pada mata pelajaran geografi. Penelitian ini adalah penelitian dan pengembangan (RD) yang menggunakan model ADDIE. Prosedur pengembangan meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Tahap analisis dan desain, dilakukan survei di lapangan untuk menganalisis kebutuhan siswa. Tahap desain disesuaikan dengan kebutuhan dalam kegiatan pembelajaran. Tahap pengembangan, validasi ahli model dan materi, kemudian dilakukan revisi produk. Tahap implementasi di kelas XI IPS SMA Assalaam pada 17 siswa. Hasil penelitian ini adalah sebagai berikut. (1) Model blended learning menggunakan aplikasi Edmodo berdasarkan tahapan komponen-komponen model. (2) Model blended learning dinyatakan layak berdasarkan hasil validasi ahli materi dengan skor 3,65 dan ahli model dengan skor 3,64 dengan kategori sangat baik. (3) Keefektifan model blended learningdibuktikan melalui peningkatan hasil belajar siswa dari 55,29 menjadi 88,65. Respon siswa secara umum menanggapi positif.Kata Kunci: model blended learning, Edmodo, geografi DEVELOPING A BLENDED LEARNING MODEL USING THE EDMODO APPLICATION IN GEOGRAPHY SUBJECT MATTER OF SENIOR HIGH SCHOOLSAbstractThis research study aims to produce (1) the blended learning model using Edmodo which can improve learning outcomes and motivation in geography subject matter, (2) the appropriateness level of the blended learning model using Edmodo which can improve learning outcomes and motivation in geography subject matter, and (3) the effectiveness of the blended learning model using Edmodo in geography subject matter. This study was research and development (RD) using the ADDIE model. The procedure of the development included the steps of analysis, design, development, implementation, and evaluation. In the analysis and design steps, a survey was conducted in the field to analyze the student’s needs in the learning. The development step, a validation was done by the model and materials experts which resulted in the initial revision of the product. In the implementation step, the teaching and learning in class XI social sciences of SMA Assalaam to 17 students. The result of the study is as follows. (1) The blended learning model using the Edmodo application viewed from its components. (2) The blended learning model using the Edmodo application fulfills the appropriateness criteria based on the result of the validity test from the material expert with the mean score of 3.65 and that from the model expert with the mean score of 3.64 which is in a very good category. (3) The effectiveness of the blended learning model was proved by the increasing learning achievements of the students from 55.29 to 88.65. In general, the students responded to the blended learning model positively.Keywords: blended learning model, Edmodo, geography